2018
DOI: 10.1016/j.joco.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional estimates of prevalence of refractive errors: Systematic review and meta-analysis

Abstract: PurposeThe aim of the study was a systematic review of refractive errors across the world according to the WHO regions.MethodsTo extract articles on the prevalence of refractive errors for this meta-analysis, international databases were searched from 1990 to 2016. The results of the retrieved studies were merged using a random effect model and reported as estimated pool prevalence (EPP) with 95% confidence interval (CI).ResultsIn children, the EPP of myopia, hyperopia, and astigmatism was 11.7% (95% CI: 10.5–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
254
5
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(328 citation statements)
references
References 154 publications
16
254
5
14
Order By: Relevance
“…Comparison of these results to epidemiological work is challenging given: (1) the small sample; (2) the use of the non‐cycloplegic Spot Photoscreener as an estimate of refraction; and (3) the difference between cut‐offs used in epidemiological work compared to that used for clinical referral . With these caveats in mind, the refraction data suggest that Tongan school children experience lower levels of myopia than children from developed parts of South East Asia, with our results being more in line with the rates of myopia reported in other Pacific Islands .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Comparison of these results to epidemiological work is challenging given: (1) the small sample; (2) the use of the non‐cycloplegic Spot Photoscreener as an estimate of refraction; and (3) the difference between cut‐offs used in epidemiological work compared to that used for clinical referral . With these caveats in mind, the refraction data suggest that Tongan school children experience lower levels of myopia than children from developed parts of South East Asia, with our results being more in line with the rates of myopia reported in other Pacific Islands .…”
Section: Discussionsupporting
confidence: 56%
“…While the data suggested low rates of myopia, there appeared to be higher levels of mild astigmatism compared to international norms . It has been reported that astigmatism is associated with keratoconus, and that Pacific students in New Zealand high schools have higher rates of keratoconus than their European peers .…”
Section: Discussionmentioning
confidence: 69%
“…11 On the other hand, our finding agrees with Hashemi H (2017) finding in systematic review and meta-analysis that astigmatism was the most common refractive error in children. 12 This variation can be explained by using different methods in the evaluation of RE type. In the present study, we used the (Plusoptix A12 R USA manufactured tool) photorefractory device which gives an accurate evaluation of RE and better detection of astigmatism than retinoscopy Study limitation is the unequal number of boys and girls; girls had a higher participation rate both in governmental and non-governmental school.…”
Section: Discussionmentioning
confidence: 99%
“…Usually stratification is required for covariates that affect measurements such as age, ethnicity and refractive error. For myopia, this is a challenge because of the large regional variation in refractive error prevalence 22. As such the normative database in OCT systems will not optimally reflect the patient population in regions where myopia and PM are highly prevalent, such as in East Asia.…”
Section: Introductionmentioning
confidence: 99%